2012
DOI: 10.1074/jbc.m111.316125
|View full text |Cite
|
Sign up to set email alerts
|

AMF-26, a Novel Inhibitor of the Golgi System, Targeting ADP-ribosylation Factor 1 (Arf1) with Potential for Cancer Therapy

Abstract: Background: Golgi is a potential target for cancer treatment, but no inhibitor became an anticancer drug.Results: Using a unique bioinformatics approach, we identified a novel Golgi inhibitor, AMF-26, targeting Arf1 activation and possessing potent antitumor activity.Conclusion: AMF-26 is a promising new anticancer drug lead.Significance: Our data indicate that Arf1 activation is a promising target for cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 55 publications
2
83
0
2
Order By: Relevance
“…ADP ribosylation factor 1 (Arf1), a small GTPase and a member of Ras superfamily (13,14), is required for maintenance of Golgi structure and function via formation of complex I (COPI) or clathrin-coated vesicles transported among the endoplasmic reticulum (ER), Golgi, and post-Golgi (15)(16)(17)(18)(19). We previously demonstrated that M-COPA (2-methylcoprophilinamide, also called "AMF-26") suppressed Arf1-mediated vesicle transport, disrupted the structure of the Golgi apparatus, and exerted antitumor activity in vivo against tumors xenografted into mice (20). In fact, M-COPA has been shown to inhibit secretion of intercellular adhesion molecule-1 (ICAM-1) and cell surface expression of VEGFR-2 (21).…”
Section: Introductionmentioning
confidence: 99%
“…ADP ribosylation factor 1 (Arf1), a small GTPase and a member of Ras superfamily (13,14), is required for maintenance of Golgi structure and function via formation of complex I (COPI) or clathrin-coated vesicles transported among the endoplasmic reticulum (ER), Golgi, and post-Golgi (15)(16)(17)(18)(19). We previously demonstrated that M-COPA (2-methylcoprophilinamide, also called "AMF-26") suppressed Arf1-mediated vesicle transport, disrupted the structure of the Golgi apparatus, and exerted antitumor activity in vivo against tumors xenografted into mice (20). In fact, M-COPA has been shown to inhibit secretion of intercellular adhesion molecule-1 (ICAM-1) and cell surface expression of VEGFR-2 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Other recently identified exocytosis inhibitors, such as AMF-26 and LM11, have been designed to specifically impair the interaction between the ARF1 GTPase and its GEFs in mammals. Although the chemical structure of AMF-26 differs from that of BFA, this compound induces disruption of the cis-and transGolgi, targeting the activation of ARF1 GTPase (Ohashi et al, 2012). To date, BFA is known to inhibit only large but not smalland medium-sized ARF-GEFs (Anders and JĂŒ rgens, 2008).…”
Section: Chemical Effectors Of Exocytosis/secretion/ Anterograde Trafmentioning
confidence: 99%
“…A virtual screen has been designed to specifically probe the interaction between the ADP-ribosylation factor 1 (ARF1) guanosine triphosphatase (GTPase) and its guanine exchange factor (GEF) ARNO based on known crystal structures of their complex (Viaud et al, 2007). Drug sensitivity databases have also been exploited to find novel inhibitors of ARF1 GTPase activation based on functional correlation with compounds with already known properties (Ohashi et al, 2012).…”
mentioning
confidence: 99%
“…Phosphatase of regenerating liver 3 exerts a pro-migratory role through the activation of Arf1, inducing faster trafficking of integrin molecules in colorectal cancer [16]. Therefore, inhibitors of Arf1 were developed with the expectation that they would be valuable tools to study membrane trafficking and also be anticancer drug candidates [17].…”
Section: Introductionmentioning
confidence: 99%